2018
DOI: 10.2320/matertrans.t-m2017853
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Deposition of Photocatalytically Enhanced TiO<sub>2</sub> Film by Atmospheric SPPS Using Ar/N<sub>2</sub>-Vortex Plasma Jet

Abstract: In this study, as cost effective and an environmentally friendly lm deposition technology, Atmospheric Solution Precursor Plasma Spray (ASPPS) was utilized for the deposition of the photo-catalytic titanium oxide (TiO 2) lm for the fabrication process of photovoltaic devices for rural electri cation in developing countries. In addition, ethanol-diluted titanium tetra-iso-butoxide (TTIB: Ti(OC 4 H 9) 4) was used as a feedstock. N 2-dominant Ar/N 2 was also utilized as plasma working gas as well as for the eleva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…The development of Cd-free absorption materials, thus, is essential to overcome the potential environmental impact. 12,13) Werner et al reported that CIGS-type cells can reach a theoretical efficiency as high as 33%. 14) The band gap can be controlled from 1.04 to 1.68 eV by changing In or Ga composition in the film, 15) which allows the optimization of the band gap value of CIGS.…”
Section: Introductionmentioning
confidence: 99%
“…The development of Cd-free absorption materials, thus, is essential to overcome the potential environmental impact. 12,13) Werner et al reported that CIGS-type cells can reach a theoretical efficiency as high as 33%. 14) The band gap can be controlled from 1.04 to 1.68 eV by changing In or Ga composition in the film, 15) which allows the optimization of the band gap value of CIGS.…”
Section: Introductionmentioning
confidence: 99%
“…The Weibull distribution has been used as an index of uniformity for APS coatings, 7,20) but herein, it is shown that it is an effective means for high-speed and low-temperature particle processes, such as HVOF coatings. This entails that the Weibull distribution is also effective for comparison between spraying processes.…”
Section: Discussionmentioning
confidence: 99%